Reasoning About Visibility in Mirrors: A Comparison Between a Human Observer and a Camera. (August 2018) - Bertamini, Marco; Soranzo, Alessandro
Human observers make errors when predicting what is visible in a mirror. This is true for perception with real mirrors as well as for reasoning about mirrors shown in diagrams. We created an illustration of a room, a top-down view, with a mirror on a wall and objects (nails) on the opposite wall. The task was to select which nails were visible in the mirror from a given position (viewpoint). To study the importance of the social nature of the viewpoint, we divided the sample ( N = 108) in two groups. One group ( n = 54) were tested with a scene in which there was the image of a person. The other group ( n = 54) were tested with the same scene but with a camera replacing the person. Participants were instructed to think about what would be captured by a camera on a tripod. This manipulation tests the effect of social perspective-taking in reasoning about mirrors. As predicted, performance on the task shows an overestimation of what can be seen in a mirror and a bias to underestimate the role of the different viewpoints, that is, a tendency to treat the mirror as if it captures information independently of viewpoint. In terms of the comparison between person and camera, there were more errors for the camera, suggesting an advantage for evaluating a human viewpoint as opposed to an artificial viewpoint. We suggest that social mechanisms may be involved in perspective-taking in reasoning rather than in automatic attention allocation.